DECENTRALIZED SOCIAL NETWORK SERVICE USING THE WEB HOSTING SERVER FOR PRIVACY PRESERVATION - Yoonho Nam; Changhoon Lee; Youngman Jung; Woongryul Jeon; Dongho Won (Faculty of Computer Science - Universitas Indonesia, 2013)
In recent years, the number of subscribers of the social network services such as Facebook and Twitter has increased rapidly. In accordance with the increasing popularity of social network services, concerns about user privacy are also growing. Existing social network services have a centralized structure that a service provider collects all the user’s profile and logs until the end of the connection. The information collected typically useful for commercial purposes, but may lead to a serious user privacy violation. The user’s profile can be compromised for malicious purposes, and even may be a tool of surveillance extremely. In this paper, we remove a centralized structure to prevent the service provider from collecting all users’ information indiscriminately, and present a decentralized structure using the web hosting server. The service provider provides only the service applications to web hosting companies, and the user should select a web hosting company that he trusts. Thus, the user’s information is distributed, and the user’s privacy is guaranteed from the service provider.